Amber, Guinevere, and Kate photographed by Craig McDean - McDean, Craig; Augustyniak, Mathias; O'Brien, Glenn (New York : Rizzoli International Publications, 2013)
"Photographer Craig McDean captures the celebrated evolution of fashion's biggest muses: Kate Moss, Guinevere van Seenus, and Amber Valletta. With their waiflike frames and unique features that contrasted with the supermodels of the '80s, Amber, Guinevere, and Kate became the anti-supermodels that, alongside grunge, signified a global shift in culture. And Craig McDean, an artist with a talented eye for the striking and unusual, photographed them from their beginnings. McDean, whose works are praised for their conceptual and sophisticated edge, is well respected in both the photography and fashion worlds. Shot on film from 1992 through 2002, this roughly chronological volume of 150 color and black-and-white images includes never-before-published photographs, outtakes from famous shoots, and contact sheets"--Publisher's web site.
boek
Keywords: McDean, Craig